1994
DOI: 10.1007/bf00269578
|View full text |Cite
|
Sign up to set email alerts
|

Expression and distribution of fetuin in the developing sheep fetus

Abstract: Tissue distribution and developmental expression of fetuin were studied in the sheep fetus from embryonic day (E) 30 to adult (gestational period is 150 days). The presence of fetuin was demonstrated immunocytochemically using anti-fetuin antibodies; in situ hybridisation using short anti-sense oligonucleotide probes labelled with digoxigenin was used to study the ability of the developing tissue to synthesise fetuin, and reverse transcription-polymerase chain reaction (RT-PCR) was used to estimate the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…Fig. 7 illustrates the results of a typical experiment in which spontaneous apatite formation from supersaturated solutions of CaCl 2 and Na 2 HPO 4 was measured as incorporation of 45 Ca into the insoluble salt pellet. The precipitation reactions proceeded for 30 min at 37°C either in the absence of serum (control) or in the presence of 10% dialyzed serum from wildtype Ahsg ϩ/ϩ , heterozygous Ahsg ϩ/Ϫ , or homozygous Ahsg…”
Section: Structure Of the Ahsg Gene Locus-twomentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 7 illustrates the results of a typical experiment in which spontaneous apatite formation from supersaturated solutions of CaCl 2 and Na 2 HPO 4 was measured as incorporation of 45 Ca into the insoluble salt pellet. The precipitation reactions proceeded for 30 min at 37°C either in the absence of serum (control) or in the presence of 10% dialyzed serum from wildtype Ahsg ϩ/ϩ , heterozygous Ahsg ϩ/Ϫ , or homozygous Ahsg…”
Section: Structure Of the Ahsg Gene Locus-twomentioning
confidence: 99%
“…Inhibition of Apatite Formation-To estimate the inhibition of salt precipitation by serum, assays were done in 20 mM Tris, pH 7.4, 100 mM NaCl, 1.6 mM Na 2 HPO 4 , and 4.8 mM CaCl 2 containing a trace amount of 45 CaCl 2 . Sera were dialyzed by repeated spin dialysis against incubation buffer using Microcon 10 centrifuge concentrators (Amicon, Inc.).…”
Section: Cloning Of the Mouse Fetuin Gene And Construction Of A Replamentioning
confidence: 99%
“…In the adult mouse, AHSG mRNA was detected mainly in the liver and also in the adrenal gland, stomach, heart and placenta by Northern blot analysis (Yang et al, 1992). In the adult sheep fetuin was detected in the liver, spleen, lymph node, skeletal muscle and bone marrow by immunocytochemistry but not in the central nervous system, kidney, heart and lung (Dziegielewska et al, 1996;Saunders et al, 1994). In the newborn rat, fetuin was observed in the liver, pancreas, cerebral cortex, blood vessels, cartilage and bone, smooth muscle, spleen, bone marrow and kidney by immunocytochemistry but not in the lung and adrenal gland (Terkelsen et al, 1998).…”
mentioning
confidence: 99%
“…In mouse embryo, fetuin-A transcript could also be detected in a number of developing tissues and organs other than hepatic tissue, such as heart, lung, kidney, nervous system, and limb buds during the particular stages (Yang et al 1992). In fetal neonatal rats and fetal sheep, the presence of fetuin-A mRNA was also found in many of the germinal cell populations of developing tissues and organs including brain, kidney, haemopoietic liver, early gastrointestinal epithelium, bone, and muscle (Saunders et al 1994;Terkelsen et al 1998), and its protein was predominantly in the developing central and peripheral nervous system, cerebrospinal fluid, and plasma (Kitchener et al 1999;Dziegielewska et al 2000). It has been demonstrated that fetuin-A plays important roles during developmental processes, including osteogenesis, myotubule (Yang et al 1992), fetal brain, and nervous system development (Kitchener et al 1999;Dziegielewska et al 2000).…”
Section: Introductionmentioning
confidence: 96%
“…Fetuin-A was first identified in fetal cow in 1944 (Pedersen 1944). In recent years, fetuin-A homologs have been cloned in sheep, pigs, cows, humans, mice, gerbils, and rats (Auberger et al 1989;Rauth et al 1992;Saunders et al 1994;Goto et al 1997;Brown and Dziegielewska 1997). Fetuin-A has been shown to function in many physiological aspects, such as fatty acid transport (Cayatte et al 1990), regulation of insulin activity and hepatocyte-growth-factor activity (Mathews et al 2002;Ohnishi et al 1997), response to systemic inflammation (Ombrellino et al 2001), and inhibition of unwanted mineralization (Schinke et al 1996;Heiss et al 2003;Schäfer et al 2003).…”
Section: Introductionmentioning
confidence: 99%